Markups and financial shocks - Philipp Meinen; Ana Cristina Soares (Deutsche Bundesbank, 2021)
This paper analyses the impact of financial frictions on markup adjustments at the firm level. We use a rich panel data set that matches information on banking relationships with firm-level data. By relying on insights from recent contributions in the literature, we obtain exogenous credit supply shifters and markups that are both firm specific and time varying. We uncover new findings at this level. In particular, firms more exposed to liquidity risks tend to raise markups in response to negative bank-loan supply shocks, while less exposed firms generally reduce them. Further empirical analyses suggest that our findings are mostly consistent with models featuring a sticky customer base, where financially constrained firms have an incentive to raise markups in order to sustain liquidity. Our results have important economic implications regarding the cyclicality of the aggregate markup.
Keywords: L22; L11; D22; G10; G01; 330; Financial Shocks; Markups; Firm-level data